Beginning Application Development with TensorFlow and Keras : Learn to design, develop, train, and deploy TensorFlow and Keras models as real-world applications /: Learn to design, develop, train, and deploy TensorFlow and Keras models as real-world applications. (2018) - Capelo, Luis
No abstract available